Establishing Anti-Sexual Violence Centers to Promote Safe Educational Environments: Mendirikan Pusat Anti Kekerasan Seksual untuk Mempromosikan Lingkungan Pendidikan yang Aman - Aida, Nur; Untoro, Untoro; Kunaeni, Kunaeni; Ramadhani, Sabrina Ayu; Fawwaz, Shafira Mufidah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Sexual violence in schools, including harassment and body shaming, undermines trust in education. Specific Background: Victims often remain silent due to threats and societal stigma, while prevention efforts in schools are underdeveloped. Knowledge Gap: Effective frameworks for addressing sexual violence in educational institutions are lacking despite existing policies. Aim: This study establishes an Anti-Sexual Violence Information Center (Anti KESEL) to educate and equip educators for prevention and response. Results: Training enhanced educators' knowledge and led to the creation of organizational structures and resources for addressing sexual violence. Novelty: A replicable model combining education, technology, and partnerships was introduced to transform schools into safer environments. Implications: The initiative fosters trust and safety in schools, with potential for broader application in combating sexual violence. Highlights: Empowering Educators: Training Pancasila MGMP members equips them to recognize, prevent, and address sexual violence effectively. Holistic Approach: Integrating education, facilitation, and technology to establish Anti KESEL as a model framework for schools. Community Collaboration: Partnering with stakeholders ensures sustainable support and broader impact in combating sexual violence. Keywords: Education, Prevention, Sexual Violence, Anti KESEL